2022
DOI: 10.2196/35828
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Internet Use and the Use of Digital Health Tools: Secondary Analysis of the 2020 Health Information National Trends Survey

Abstract: Background The COVID-19 pandemic increased the use of digital tools in health care (eg, patient portal, telemedicine, and web-based scheduling). Studies have shown that older individuals, racial/ethnic minority groups, or populations with lower educational attainment or income have lower rates of using digital health tools. Digitalization of health care may exacerbate already existing access barriers in these populations. Objective This study evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Before COVID-19, cancer survivors aged ≥75 years were least likely to practice OPPC via email, the internet, a tablet, or a smartphone. This was also observed among adults without a history of cancer in this study, which aligns with the previous literature [ 28 ]. Prior studies suggest that adults aged 65 years and older had less interest in exchanging medical information online with providers [ 52 ], less frequently used social media for health communication [ 53 ], and less frequently used the internet to search for health information [ 54 ] compared to younger generations.…”
Section: Discussionsupporting
confidence: 93%
“…Before COVID-19, cancer survivors aged ≥75 years were least likely to practice OPPC via email, the internet, a tablet, or a smartphone. This was also observed among adults without a history of cancer in this study, which aligns with the previous literature [ 28 ]. Prior studies suggest that adults aged 65 years and older had less interest in exchanging medical information online with providers [ 52 ], less frequently used social media for health communication [ 53 ], and less frequently used the internet to search for health information [ 54 ] compared to younger generations.…”
Section: Discussionsupporting
confidence: 93%
“…While telemedicine was available before the pandemic, 27 29 it rapidly expanded at the onset of the COVID-19 pandemic. 30 32 Overall, the ability to access care in multiple ways has the potential to improve access, especially among women and younger populations 3 , 4 who may feel uncomfortable receiving care in-person, require childcare, or lack the ability to take time off work. For many, especially those living in rural or underserved areas, the time and travel savings are a significant benefit despite growing literature about inequitable access to broadband in rural locations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have tried to compare and explain some facets of socioeconomic status differences but with limited evidence. They have shown that people with lower income and education levels, and higher ages, are less inclined to use digital health tools, including telemedicine [ 53 , 54 ]. A systematic review found that older adults and those with lower education level were the least inclined to adopting telemedicine, which correlated with 29% of the responses for lack of UI [ 55 ].…”
Section: Discussionmentioning
confidence: 99%